2012
DOI: 10.1371/journal.pone.0045020
|View full text |Cite
|
Sign up to set email alerts
|

Acid Sphingomyelinase Gene Knockout Ameliorates Hyperhomocysteinemic Glomerular Injury in Mice Lacking Cystathionine-β-Synthase

Abstract: Acid sphingomyelinase (ASM) has been implicated in the development of hyperhomocysteinemia (hHcys)-induced glomerular oxidative stress and injury. However, it remains unknown whether genetically engineering of ASM gene produces beneficial or detrimental action on hHcys-induced glomerular injury. The present study generated and characterized the mice lacking cystathionine β-synthase (Cbs) and Asm mouse gene by cross breeding Cbs+/− and Asm+/− mice. Given that the homozygotes of Cbs−/−/Asm−/− mice could not surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…This resistance to alcohol-mediated ER stress was observed despite an increase in plasma Hcy to levels similar to those found in alcohol-fed wild type littermates, regardless of whether alcohol was administered orally or intragastrically, suggesting that resistance to alcohol-induced ER stress in the absence of ASMase is independent of hyperhomocysteinemia (Baulies et al, unpublished observations) [6]. Consistent with these findings, Boini et al recently showed that ASMase ablation prevented Hcy-induced glomerular injury in CBS +/À mice, a genetic model of hyperhomocysteinemia and increased plasma Hcy levels [118,119]. In this model, ASMase silencing prevented Hcy-induced ceramide generation, indicating that ASMase activation by Hcy is a major pathway of glomerular ceramide generation.…”
Section: Asmase Regulates Er Stressmentioning
confidence: 74%
“…This resistance to alcohol-mediated ER stress was observed despite an increase in plasma Hcy to levels similar to those found in alcohol-fed wild type littermates, regardless of whether alcohol was administered orally or intragastrically, suggesting that resistance to alcohol-induced ER stress in the absence of ASMase is independent of hyperhomocysteinemia (Baulies et al, unpublished observations) [6]. Consistent with these findings, Boini et al recently showed that ASMase ablation prevented Hcy-induced glomerular injury in CBS +/À mice, a genetic model of hyperhomocysteinemia and increased plasma Hcy levels [118,119]. In this model, ASMase silencing prevented Hcy-induced ceramide generation, indicating that ASMase activation by Hcy is a major pathway of glomerular ceramide generation.…”
Section: Asmase Regulates Er Stressmentioning
confidence: 74%
“…We further explored the molecular mechanisms mediating the production of these novel effects of Nlrp3 inflammasome in ECs. The production of ROS was shown to be one of the major early factors mediating death factor-induced endothelial injury (5,6,40,49,50). NADPH oxidase-derived ROS associated with ceramide-enriched membrane raft clustering (21,47,52) were found to primarily contribute to the death factor or adipokine visfatin-mediated endothelial dysfunction (13,17,46,48,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, findings in mice deficient in cystathionine β-synthase have shown that the link between hyperhomocysteinemia and the subsequent glomerular injury is dependent on acid sphingomyelinase (ASMase)-mediated ceramide generation [77•]. Moreover, exogenous ASMase has been shown to directly induce ER stress in isolated hepatocytes by disrupting ER Ca 2+ homeostasis, while the effects upon the addition of homocysteine in causing ER stress were modest and required suprapharmacological doses [63•].…”
Section: Er Stress and Its Mitochondrial Linkmentioning
confidence: 99%